Hello, Red Fox - Carle, Eric. (New York : Simon & Schuster Books for Young Readers, 1998)
Guests at Little Frog's birthday party include the red fox, the purple butterfly, the orange cat, and other colorful animals. The illustrations are designed to demonstrate the concept of complementary colors.
Keywords: Color -- Fiction; Frogs -- Fiction; Animals -- Fiction; Parties -- Fiction; Birthdays -- Fiction